Legislation of Renewable Energy Sources In Slovakia / Legislatívna Úprava Obnoviteľných Zdrojov Energie Na Slovensku - Marišová, Eleonóra; Ilková, Zuzana; Palšová, Lucia; Mandalová, Kristína (EU agrarian law, 2015)
Growing renewable energy plants on agricultural land and its further energy usage presents a significant importance for implementing long-term strategy of Slovakia in the area of acquisition and use of renewable energy sources (RES). Renewable energy plants together fulfil the objectives of Europe 2020 strategy and contributes to diversification of energy resources. The paper draws on the EU and national legislation regulating RES. Directive 2009/28/EC of the European parliament and of the Council of 23 April 2009 on the promotion of the use of energy from renewable sources and amending and subsequently repealing Directives 2001/77/EC and 2003/30/EC are analysed. Broadly, the topic of the renewable energy resources is integrated in Rural Development Program 2014 - 2020. More specifically, Biomass Action Plan 2008- 2013, Strategy of higher use of the renewable energy resources in Slovakia and Strategy of energy security of Slovakia till 2030 have been adopted. Sustainable use of agricultural land, its management and use, as well as the protection of its quality and functions are regulated by Act No. 220/2004 Coll. on the protection and use of agricultural land and amending the Act no. 245/2003 Coll. on integrated prevention and control of environmental pollution and amending certain acts as amended which came into the force 1. May 2004. Act. No. 57/2013 Coll. with is in effect from 1 April 2013, establishes the principles and procedure for the establishment of plantations of fast-growing trees on agricultural land. Slovak legislation introduced a register for fast-growing trees in Slovak territories at each district office, Land and Forest Department in Slovakia (72). The survey at registers shows that this legislation promoted the farmers to start to use marginal land for fast-growing trees. Pestovanie energetickych rastlin a drevin na poľnohospodarskej pode a ďalšie využitie ich energie predstavuje zasadny vyznam pre realizaciu dlhodobej strategie Slovenska v oblasti ziskavania a využivania obnoviteľnych zdrojov energie (OZE). Energeticke rastliny spĺňaju ciele strategie Europa 2020 a prispievaju k diverzifi kacii energetickych zdrojov. Prispevok vychadza z pravnych predpisov EU a narodnej legislativy upravujucej OZE. Analyzovane su Smernica 2009/28/ES Europskeho parlamentu a Rady z 23. aprila 2009 o podpore využivania energie z obnoviteľnych zdrojov a o zmene a naslednom zrušeni smernic 2001/77/ES a 2003/30/ES. Tema obnoviteľnych zdrojov energie je integrovana do Programu rozvoja vidieka 2014 - 2020. Konkretne Akčny plan pre biomasu 2008-2013, Strategia vyššieho využitia obnoviteľnych zdrojov energie na Slovensku a Strategia energetickej bezpečnosti Slovenska bola prijata až do roku 2030. Trvalo udržateľne využivanie poľnohospodarskej pody, jeho riadenie a využivanie, ako aj ochrana jeho kvality a funkcie su upravene zakonom č 220/2004 Zb. o ochrane a využivani poľnohospodarskej pody a ktorym sa meni zakon č. 245/2003 Zb., o integrovanej prevencii a kontrole znečisťovania životneho prostredia a o zmene niektorych zakonov v zneni neskoršich predpisov, ktory nadobudol učinnosť 1. maja 2004. Zakon č. 57/2013 Zb., ktory je platny od 1. aprila 2013, stanovuje zasady a postup zriaďovania plantaži rychlorastucich drevin na poľnohospodarskej pode. Slovenska pravna uprava zaviedla register rychlo rastucich drevin na každom okresnom urade (72), na pozemkovom a lesnom odbore na Slovensku. Prieskum tychto registrov ukazuje, že tato pravna uprava podporuje poľnohospodarov, aby začali použivať marginalne pody pre rychlo rastuce dreviny.